Pomen zgodnjih kliničnih in biokemičnih sprememb pri esencialni arterijski hipertenziji - Bedenčič, Klemen (Medicinski razgledi, 2011)
Backgrounds. Essential arterial hypertension is one of the most common chronicdiseases of the circulation system. It is of ten linked to metabolic syndrome with corresponding dinical and biochemical changes of blood. We evaluated dinical and biochemical changes in serum in young healthy normotensive offspring of subjects with essential arterial hypertension in comparison to control group. Methods. This cross-sectional study induded 77 subjects, 38 of whom were normotonics with familial trait and 39 age matched controls without familial tra it. We evaluated anthropometric indexes and measured blood pressure. Serum concentrations of glucose, cholesterois, triglycerides, adiponectin and asymetric dymetilarginine were measured by enzymatic method, while insulin and C reactive protein were assessed by radio-immunoassay kit. Results. Subjects with familial trait had increased anthropometric indexes - body mass index and higher systolic blood pressure. They had also significantly higher concentrations of glucose, total and low-density lipoproteins cholesterol, triglycerides, C reactive protein, insulin and significantly lower concentrations of adiponectin however there were no differences in concentrations of asymetric dymetil arginine. In all subjects values of insulin was positively correlated with familial trait, bodymass index, systolic blood pressure, concentration of triglycerides, glucose, C reactive protein and negatively correlated to adiponectin concentrations. Multiple regression model analysis revealed independent influence of positive family history, male gender, body mass index, triglyceride and adi ponectin concentrations on hyperinsulinaemia. Conclusions. Subjects with familial trait differed from control group not onlyin blood pressure level, but also in certain dinical parameters and biochemical blood parameters. These parameters are a constitutive part of metabolic syndrome. (Abstract truncated at 2000 characters)
Keywords: Holesterol; Hypertension; Genetics; Krvni sladkor; Prehranjenost, stanje; Diagnosis; Nutritional Status; Hipertenzija; Blood Glucose; Inzulin; Insulin; Adipociti; Cholesterol; Presečne študije; Odrasli; Triglycerides; Trigliceridi; C-Reactive Protein; C-reaktivna beljakovina; Insulin Resistance; Insulinska rezistenca; Adipocytes; Secretion; Krvni pritisk; arterijska hipertenzija; Blood Pressure; Cross-Sectional Studies; inzulinska rezistenca; presnovni sindrom; Adult; biokemija; sestava krvi